Metastasis of cN0 Papillary Thyroid Carcinoma of the Isthmus to the Lymph Node Posterior to the Right Recurrent Laryngeal Nerve - Du, Wei; Fang, Qigen; Zhang, Xu; Dai, Liyuan (Frontiers in Endocrinology, 2021)
Objective: The association between metastasis to the lymph node posterior to the right recurrent laryngeal nerve (LN-prRLN) and cN0 papillary thyroid carcinoma (PTC) located in the thyroid isthmus remains unknown; therefore, our goal was to analyze the characteristics of LN-prRLN metastasis of cN0 PTCs of the thyroid isthmus and determine its potential predictors. Patients and methods: this retrospective study included patients who underwent bilateral central neck dissection between January 2018 and January 2021. The specimen was divided into five groups of prelaryngeal lymph node (LN), pretracheal LN, left paratracheal LN, lymph node anterior to the right recurrent laryngeal nerve (LN-arRLN), and LN-prRLN. Univariate and multivariate analyses were used to assess the association between the clinical pathologic variables and LN-prRLN metastases. Surgical complications were presented descriptively. Results: A total of 357 patients were included, LN-prRLN metastasis occurred in 23 (6.4%) patients, and LN-prRLN was positive only when there were other LNs metastases, especially LN-arRLN metastases. Other independent risk factors for LN-prRLN included foci numbers ≥2, tumor size ≥5.0 mm, and extrathyroidal extensions. The rates of permanent hypoparathyroidism and vocal cord paralysis were 1.1% and 2.0%, respectively. Conclusion: LN-prRLN metastases should not be ignored in cN0 PTC located in the thyroid isthmus; however, its dissection is a safe procedure, and the status of LN-arRLN can be a reliable predictor for LN-prRLN metastases.